2010
DOI: 10.1261/rna.2224411
|View full text |Cite
|
Sign up to set email alerts
|

Structural model of the p14/SF3b155·branch duplex complex

Abstract: Human p14 (SF3b14), a component of the spliceosomal U2 snRNP, interacts directly with the pre-mRNA branch adenosine within the context of the bulged duplex formed between the pre-mRNA branch region and U2 snRNA. This association occurs early in spliceosome assembly and persists within the fully assembled spliceosome. Analysis of the crystal structure of a complex containing p14 and a peptide derived from p14-associated SF3b155 combined with the results of cross-linking studies has suggested that the branch nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
1
21
2
Order By: Relevance
“…There seems to be flexibility in the choice of the BP adenosine, as either one of the two A residues present in the consensus BPS can be used as a BP, depending on the intron in question 52. BPS recognition is likely stabilized by proteins of the SF3b complex, which is present in both spliceosomes (Table 1), and is known to bind to the BPS in the major spliceosome, with the protein factor p14 shielding the BP adenosine from premature activation 39,53,54. U12‐type introns do not have PPTs, and U2AF is not required for the recognition of U12‐type introns 55.…”
Section: Spliceosome Assembly and Catalysismentioning
confidence: 99%
“…There seems to be flexibility in the choice of the BP adenosine, as either one of the two A residues present in the consensus BPS can be used as a BP, depending on the intron in question 52. BPS recognition is likely stabilized by proteins of the SF3b complex, which is present in both spliceosomes (Table 1), and is known to bind to the BPS in the major spliceosome, with the protein factor p14 shielding the BP adenosine from premature activation 39,53,54. U12‐type introns do not have PPTs, and U2AF is not required for the recognition of U12‐type introns 55.…”
Section: Spliceosome Assembly and Catalysismentioning
confidence: 99%
“…Hence, we modeled the branch point duplex (BPD) containing U12 snRNA and pre-mRNA, including the BPA, using an available crystal structure of BPD (PDB ID: 1I9X) 84 and prior knowledge of U12 snRNA: pre-mRNA base pairing. 85 The information on the recognition of BPA by p14 was collated from multiple sources 9,30 and the p14-BPD complex structure was modeled using a restrained docking procedure (see Materials and Methods). Further, we found that the p14-BPD docked complex structures fitted snugly into the groove above p14 density surface, when fitted in the U11/U12 di-snRNP cryo-EM map.…”
Section: U12 Snrna and Branch Point Duplex Binding To Sf3b Open Formmentioning
confidence: 99%
“…8 It forms a dynamic and integral part of 4 intermediary complexes (A, B, B Ã and B act ). Previous studies have revealed various roles for SF3b complex including i) recognition of branch point adenosine 9 and promotion of stable interaction for U2 and U11/U12 di-snRNP to pre-mRNA, 10 ii) prevention of premature splicing 10 and iii) interaction with snRNAs and pre-mRNA. 11,12 The complex is made of 7 proteins, namely, p14, SF3b49, SF3b145, SF3b155, SF3b10, SF3b130 and SF3b14b.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations